Fósforo na produtividade e qualidade de sementes de feijão Carioca Precoce cultivado no período das águas - Zucareli, Claudemir; Prando, Andre Mateus; Ramos Junior, Edison Misses; Nakagawa, Joao [UNESP] (Univ Federal Ceara, Dept Geol, 2011)
Common bean is an important crop in Brazilian agriculture and phosphorus (P) deficiency is one of the most yield limiting factors for this crop, thus plant P-deficiency can hamper the seed physiological quality. The objective of this study was to evaluate the productivity and quality of common bean seeds cv. Carioca Precoce cultivated during the rainy season in response to phosphate fertilizer. Six levels of P (0; 30; 60; 90; 120 and 150 kg of P2O5 had), with five replications, were applied in the groove of sowing as triple superphosphate. The seeds yield, at the experimental plot, was determined by the dry weight. Seed quality was evaluated through the following determinations: 100-seed mass, seed moisture content, germination, first counting, moisture content after accelerated aging, germination after accelerated aging, electrical conductivity, seedling emergence in the field and seedlings dry weight. The productivity of beans seeds 'Carioca Precoce' cultivated during the rainy season increased linearly as related to phosphorus rates. The 100-seed mass and the physiological quality of seeds have not changed by increasing of P levels.
Phosphorus on the productivity and seed quality of bean Carioca Precoce cultivated during the rainy season
Keywords: Phaseolus vulgaris L; Phosphate fertilizer; Nutrient; Germination; Vigor